Root and Nodulation Phenotypes of the Ethylene-Insensitive Sickle Mutant of Medicago truncatula - JOKO PRAYITNO (Bogor Agricultural University, Indonesia, 2010)
The sickle (skl) mutant of the model legume Medicago truncatula is an ethylene-sensitive mutant that have a ten-fold increase in nodule numbers. The nodulation and root phenotypes of the skl mutant were investigated and further characterised. The skl mutant had longer roots than the wild type, but when inoculated with Sinorhizobium, its root length was reduced to the level of wild type. Furthermore, lateral root numbers in uninoculated skl were similar to those in uninoculated wild type. However, when the root tips were decapitated, fewer lateral roots formed in skl than in wild type. Nodule numbers of the skl mutant were significantly reduced by low nitrate concentration (2.5 mM). These results suggest that skl mutant has alterations in both root and nodule development.